JUSTICE IN HUMAN RIGHTS COURTS: INTEGRATING THE CONCEPT OF ISLAMIC JUDICIARY AND THE PRINCIPLES OF INTERNATIONAL LAW - Ahmad Iffan; Mustafid (Muadalah : Jurnal Hukum, 2025)
This study aims to analyze the concept of justice in Human Rights Courts through the integration of Islamic judicial principles and international legal norms. The research employs a normative-comparative juridical approach by examining primary and secondary legal sources, including international human rights instruments, Islamic legal provisions, and jurisprudential practices of national and international human rights courts. The analysis applies a qualitative and hermeneutic legal method to identify the points of convergence between the two systems in achieving substantive justice. The findings reveal that both Islamic and international legal systems share an ethical foundation centered on human dignity and moral accountability for human rights violations. The integration of these legal traditions strengthens the moral legitimacy and effectiveness of human rights adjudication, particularly in Muslim-majority countries. This research highlights the importance of cross-system legal dialogue in developing a universal paradigm of justice that transcends formal legality and embodies deeper humanistic and spiritual values